Three-component coupling of aryl iodides, allenes, and aldehydes catalyzed by a Co/Cr-hybrid catalyst - Komeyama, Kimihiro; Sakiyama, Shunsuke; Iwashita, Kento; Osaka, Itaru; Takaki, Ken (Beilstein Journal of Organic Chemistry, 2018)
The cobalt/chromium-catalyzed three-component coupling of aryl iodides, allenes, and aldehydes has been developed to afford multi-substituted homoallylic alcohols in a diastereoselective manner. Control experiments for understanding the reaction mechanism reveal that the cobalt catalyst is involved in the oxidative addition and carbometalation steps in the reaction, whereas the chromium salt generates highly nucleophilic allylchromium intermediates from allylcobalt species, without the loss of stereochemical information, to allow the addition to aldehydes.
Keywords: chromium; cobalt; diastereoselective; homoallyl alcohols; hybrid catalyst; three-component coupling

(untitled) - Takai, K. (Bull. Chem. Soc. Jpn., 2015)

(untitled) - Flynn, A. B.; Ogilvie, W. W. (Chem. Rev., 2007)

Modern Organonickel Chemistry - Tamaru, Y. (Wiley-VCH, 2005)

(untitled) - Okude, Y.; Hirano, S.; Hiyama, T.; Nozaki, H. (J. Am. Chem. Soc., 1977)

(untitled) - Jin, H.; Uenishi, J.; Christ, W. J.; Kishi, Y. (J. Am. Chem. Soc., 1986)

(untitled) - Takai, K.; Tagashira, M.; Kuroda, T.; Oshima, K.; Utimoto, K.; Nozaki, H. (J. Am. Chem. Soc., 1986)

(untitled) - Fürstner, A.; Shi, N. (J. Am. Chem. Soc., 1996)

(untitled) - Takai, K.; Nitta, K.; Fujimura, O.; Utimoto, K. (J. Org. Chem., 1989)

(untitled) - Usanov, D. L.; Yamamoto, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Takai, K.; Matsukawa, N.; Takahashi, A.; Fujii, T. (Angew. Chem., Int. Ed., 1998)

(untitled) - Takai, K.; Toratsu, C. (J. Org. Chem., 1998)

(untitled) - Xiong, Y.; Zhang, G. (J. Am. Chem. Soc., 2018)

(untitled) - Komeyama, K.; Kashihara, T.; Takaki, K. (Tetrahedron Lett., 2013)

(untitled) - Komeyama, K.; Okamoto, Y.; Takaki, K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Komeyama, K.; Asakura, R.; Fukuoka, H.; Takaki, K. (Tetrahedron Lett., 2015)

(untitled) - Komeyama, K.; Kiguchi, S.; Takaki, K. (Chem. Commun., 2016)

(untitled) - Hopkins, C. D.; Malinakova, H. C. (Org. Lett., 2004)

(untitled) - Fillon, H.; Gosmini, C.; Périchon, J. (J. Am. Chem. Soc., 2003)

(untitled) - Daly, J. J.; Sneeden, R. P. A.; Zeiss, H. H. (J. Am. Chem. Soc., 1966)

(untitled) - Kanno, K.-i.; Liu, Y.; Iesato, A.; Nakajima, K.; Takahashi, T. (Org. Lett., 2005)

(untitled) - Ito, H.; Ito, S.; Sasaki, Y.; Matsuura, K.; Sawamura, M. (J. Am. Chem. Soc., 2007)

(untitled) - Ohmiya, H.; Makida, Y.; Li, D.; Tanabe, M.; Sawamura, M. (J. Am. Chem. Soc., 2010)

(untitled) - Yoshida, Y.; Murakami, K.; Yorimitsu, H.; Oshima, K. (J. Am. Chem. Soc., 2010)

(untitled) - Hiyama, T.; Kimura, K.; Nozaki, H. (Tetrahedron Lett., 1981)